Volume 2: Design, Construction, and Operation Innovations; Compression and Pump Technology; SCADA, Automation, and Measurement; 1996
DOI: 10.1115/ipc1996-1883
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Models for Static Denting and Dynamic Puncture of Gas Transmission Linepipe and Their Validation

Abstract: Gas transmission pipe resistance to external damage is a subject of great attention at Gaz de France and in Europe. Existing results cover part of the necessary criteria for the residual life of damaged pipelines, but more knowledge is needed on defect creation. We propose to complement existing experimental work which is limited to the explored range of parameters by validated numerical models. The first, simple static denting model aims at optimizing the conditions for calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This project was completed using both laboratory based full-scale experimental work and numerical study using non-linear finite element method (FEM). NPS 30 X70 grade [24] steel pipe used in oil and gas transmission A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 5 pipelines was chosen to make the test specimens. The outer diameter of the pipe is 762 mm (30 in) and the thickness of the pipe wall is 8.5 mm (0.33 in) and hence, the outer diameter-tothickness ratio (D/t) of the pipe specimens used in the experimental work is about 90.…”
Section: Test Specimenmentioning
confidence: 99%
See 1 more Smart Citation
“…This project was completed using both laboratory based full-scale experimental work and numerical study using non-linear finite element method (FEM). NPS 30 X70 grade [24] steel pipe used in oil and gas transmission A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 5 pipelines was chosen to make the test specimens. The outer diameter of the pipe is 762 mm (30 in) and the thickness of the pipe wall is 8.5 mm (0.33 in) and hence, the outer diameter-tothickness ratio (D/t) of the pipe specimens used in the experimental work is about 90.…”
Section: Test Specimenmentioning
confidence: 99%
“…Construction and excavation activities can cause impact loads resulting in mechanical damages in onshore pipeline while anchors or trawling gear actions can cause mechanical damages in offshore pipelines. It has been reported that the failure of oil and gas transmission pipelines resulting from mechanical damages ranges from 55% in the USA to around 70% in A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 3 Europe [3][4][5][6]. In a more recent study conducted by Alberta Energy Regulator (AER), mechanical damages has been responsible for more than 53% of crude oil pipeline failure since 1990 to 2012 [2].…”
Section: Introductionmentioning
confidence: 99%
“…The European Pipeline Research Group (EPRG) first developed an empirical model [70] for predicting the fatigue life of a smooth dent. Based both on dent maximum depth and on the maximum operation stress the model calculates the fatigue life of a pipe modified by the stress concentration due to the dent using the fatigue strength-fatigue life (SN) curves for submerged arc welded pipes given in the DIN 2413 standard [71].…”
Section: Puc-rio -Certificação Digital Nº 1521424/camentioning
confidence: 99%
“…This methodology is based on the first empirical method developed by the EPRG [70] for predicting the fatigue life of an unconstrained plain dent.…”
Section: Pdam -Pipeline Defect Assessment Manualmentioning
confidence: 99%